(untitled) (International Conference on Computers in Education, 2016)
In this paper, we describe a case study of learning environment for problem-posing targeted as learners with reading disability. We have developed a learning environment for problem-posing as sentence integration that is different from usual problem-posing targeted as arithmetic word problem. In this exercise, a learner is required to select and arrange given simple sentence cards for posing problems. On the other hands, learners write problems from scratch in usual problem-posing. Because it is very difficult for learners with reading disability to write a sentence, they cannot exercise by usual problem-posing virtually even though a teacher would like to teach the arithmetic word problems to them through problem-posing exercise. However, several learners with reading disability are able to read a simple sentence. So, we assumed that these learners realize to exercise problem-posing by the problem-posing as sentence integratiom Analysis of its practical use confirmed that it is possible for them not only to pose a problem but also to learn a structure of arithmetic word problem by using our leaming environment.